Antioxidant and anti-inflammation effects of dietary phytochemicals: The Nrf2/NF-κB signalling pathway and upstream factors of Nrf2. (December 2022) - Wu, Shujian; Liao, Xiyu; Zhu, Zhenjun; Huang, Rui; Chen, Mengfei; Huang, Aohuan; Zhang, Jumei; Wu, Qingping; Wang, Juan; Ding, Yu
Abstract: Oxidative stress (OS) is created by an imbalance between reactive oxygen species and antioxidant levels. OS promotes inflammation and is associated with many diseases, such as neurodegenerative disorders, diabetes, and cardiovascular disease. Nrf2 and NF- κ B are critical in the cellular defence against OS and the regulators of inflammatory responses, respectively. Recent studies revealed that the Nrf2 signalling pathway interacts with the NF- κ B signalling pathway in OS. More importantly, many natural compounds have long been recognized to ameliorate OS and inflammation via the Nrf2 and/or NF- κ B signalling pathway. Thus, we briefly overview the potential crosstalk between Nrf2 and NF- κ B and the upstream regulators of Nrf2 and review the literature on the antioxidant and anti-inflammatory effects of dietary phytochemicals (DPs) that can activate these defence systems. The aim is to provide evidence for the development of DPs into functional food for the regulation of the Nrf2/NF- κ B signalling pathway by upstream regulators of Nrf2. Graphical abstract: Dietary phytochemicals (DPs) may exert protective effects by intervening in the Nrf2/NF- κ B pathway via activation of the upstream regulators of Nrf2. Image 1 Highlights: Nrf2 and NF- κ B are key transcription factor for OS and inflammation, respectively. There is a crosstalk between Nrf2 and NF- κ B. Upstream factors of Nrf2 are critical targets in Nrf2/NF- κ B signaling pathway. DPs can affect Nrf2/NF- κ B signaling pathway by the upstream factors of Nrf2.